2011
DOI: 10.1520/jai103632
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Online Oil Condition Monitoring Sensors and Alignment with ASTM Methods and Practices

Abstract: Oil condition monitoring is a vital part of integrated asset health management. With an increasing impetus toward real-time decision making, delays incurred in offline laboratory oil analysis are becoming less acceptable. At present, several oil quality parameters can be monitored by commercially available sensors, and active research and development programmes are being pursued by both academic and industrial researchers to develop robust, cost effective sensors for the remaining key parameters. Published (ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the previous work 610 on the fault diagnosis using oil analysis, the relationships between typical parameters of the wear debris and the wear mechanisms of machinery faults have been investigated. Based on this knowledge and other research experience reported in Lunt 11 and Yan et al, 19 this article has further developed a remote on-line fault diagnosis system using the tribological information for the industrial application on the marine diesel engines.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the previous work 610 on the fault diagnosis using oil analysis, the relationships between typical parameters of the wear debris and the wear mechanisms of machinery faults have been investigated. Based on this knowledge and other research experience reported in Lunt 11 and Yan et al, 19 this article has further developed a remote on-line fault diagnosis system using the tribological information for the industrial application on the marine diesel engines.…”
Section: Discussionmentioning
confidence: 94%
“…10 However, traditional off-line laboratory oil analysis delays the decision-making, and hence, it has limited practical application. 11 With an increasing demand for real-time execution of oil analysis, the on-line oil monitoring sensors and detection systems have attracted great interest for both academic and industrial researchers. Markova et al 12 investigated an on-line monitoring of oil viscosity using a novel vibration method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interval periods are often too lengthy to capture the critical moment just before failure [16]. Furthermore, Lunt claims that offline laboratory oil analysis is becoming less acceptable, as maintenance strategies are developing more towards real-time decision making [63]. Hence, there is an arguably a need for OEMs to improve CBM programmes by addressing these concerns.…”
Section: Monitoring Hydraulic Systems To Predict Faultsmentioning
confidence: 99%